STUDI ANALISIS MATAN HADIS TENTANG PENGUATAN JIWA DALAM MENGHADAPI MUSIBAH - Taha, Suci Rahmawati; Hakim, Ridwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the meaning of the matn of hadiths on strengthening the soul in facing affliction, classify the relevant hadith themes, and analyze their relationship with psychological resilience. This research employed a qualitative approach with a library research design. The method used was thematic hadith study (maudhu’i) through several stages: determining the theme, collecting relevant hadiths, grouping them based on the content of their matn, analyzing their meanings, and drawing conceptual conclusions. The primary data consisted of hadiths on affliction related to patience, acceptance, reliance upon Allah, supplication, gratitude, reward, expiation of sins, and faith in divine decree. Secondary data were obtained from hadith books, works on hadith studies, and relevant journal articles. The findings show that the matn of hadiths does not merely present affliction as suffering, but also as a test from Allah containing wisdom, reward, expiation of sins, and spiritual development. The dominant theme identified is patience in facing affliction, followed by affliction as a trial, reward and expiation of sins, acceptance, reliance upon Allah, supplication, gratitude, and faith in divine decree. These hadiths are relevant to psychological resilience because they shape inner strength, emotional control, acceptance of reality, optimism, hope, and closeness to Allah. Therefore, the matn of hadiths on affliction contributes to building spiritual strength and the resilience of a believer’s soul.